Hybrid integration of scalable mechanical and magnetophoretic focusing for magnetic flow cytometry - Reisbeck, Mathias; Richter, Lukas; Helou, Michael Johannes; Arlinghaus, Stephan; Anton, Birgit; van Dommelen, Ignas; Nitzsche, Mario; Bassler, Michael; Kappes, Bärbel; Friedrich, Oliver; Hayden, Oliver (Biosensors and Bioelectronics, 2018)
Time-of-flight (TOF) magnetic sensing of rolling immunomagnetically-labeled cells offers great potential for single cell function analysis at the bedside in even optically opaque media, such as whole blood. However, due to the spatial resolution of the sensor and the low flow rate regime required to observe the behavior of rolling cells, the concentration range of such a workflow is limited. Potential clinical applications, such as testing of leukocyte function, require a cytometer which can cover a cell concentration range of several orders of magnitude. This is a challenging task for an integrated dilution-free workflow, as for high cell concentrations coincidences need to be avoided, while for low cell concentrations sufficient statistics should be provided in a reasonable time-to-result. Here, we extend the spatial bandwidth of a magnetoresistive sensor with an adaptive and integratable workflow concept combining mechanical and magnetophoretic guiding of magnetically labeled targets for in-situ enrichment over a dynamic concentration range of 3 orders of magnitude. We achieve hybrid integration of the enrichment strategy in a cartridge mold and a giant-magnetoresistance (GMR) sensor in a functionalized Quad Flat No-Lead (QFN) package, which allows for miniaturization of the Si footprint for potential low-cost bedside testing. The enrichment results demonstrate that TOF magnetic flow cytometry with adaptive particle focusing can match the clinical requirements for a point-of-care (POC) cytometer and can potentially be of interest for other sheath-less methodologies requiring workflow integration.
Keywords: Giant magnetoresistance; Sensor integration; Point-of-care; Flow cytometry; Magnetophoresis